Preliminary investigation of tangelo oil Citrus paradisi Macf. x Citrus reticulata Blanco (Family Rutaceae) - Jara, Nenita S.
The fresh peel from the matured fruits of tangelo (Citrus paradise Macf. X. Citrus reticulata Blanco) was steam distilled using a Clevenger apparatus for oils lighter than water, the fresh peel gave a colorless volatile oil with a characteristic aromatic odor, with a yield of 2.5%. the oil had the following physical characteristics: specific gravity 0.8423; refractive index - 1.45948; optical rotation - 108.9873.